Exact Solutions of Steady Plane Flows of an Incompressible Fluid of Variable Viscosity in The Presence of Unknown External Force Using (ε,ψ )– or (η,ψ)-Coordinates: Rana Khalid Naeem, Asif Mansoor, Waseem Ahmed Khan - Team, Support (Thai Journal of Mathematics, 2009)
It is indicated that equations governing the steady plane motion of an incompressible fluid of variable viscosity in the presence of an external force for an arbitrary state equation admits an infinite set of solutions for the streamline pattern of the form η-f(ξ)g(ξ) = constant or ξ-f(η)g(η)=constant defined in section (3).